2020
DOI: 10.1186/s11671-019-3242-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a General Fabrication Strategy for Carbonaceous Noble Metal Nanocomposites with Photothermal Property

Abstract: This study demonstrates a simple hydrothermal method while can be generalized for controllable synthesis of noble metallic carbonaceous nanostructures (e.g., Au@C, Ag@C) under mild conditions (180-200°C), which also provides a unique approach for fabricating hollow carbonaceous structures by removal of cores (e.g., silver) via a redox etching process. The microstructure and composition of the as-achieved nanoparticles have been characterized using various microscopic and spectroscopic techniques. Cetyltrimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The main techniques for the preparation of metallic nanoparticles are reduction‐based methods (includes vigorous stirring, mild heating, and the use of a reduction agent), burst methods (synthesis of nanoparticles in organic liquids), and hydro (solvo)‐thermal (chemical reactions in solvents above their critical point at high pressure and temperature) [33] . Zhu et al (2020) reported mild condition synthesis of noble metal carbonaceous nano‐composites of Au@C. This preparation method could be applied as a general strategy for the synthesis of various carbonaceous core‐shell nanoparticles applicable in phototherapy [34] …”
Section: Photothermally Responsive Nanomaterials For Therapy Applicatmentioning
confidence: 99%
“…The main techniques for the preparation of metallic nanoparticles are reduction‐based methods (includes vigorous stirring, mild heating, and the use of a reduction agent), burst methods (synthesis of nanoparticles in organic liquids), and hydro (solvo)‐thermal (chemical reactions in solvents above their critical point at high pressure and temperature) [33] . Zhu et al (2020) reported mild condition synthesis of noble metal carbonaceous nano‐composites of Au@C. This preparation method could be applied as a general strategy for the synthesis of various carbonaceous core‐shell nanoparticles applicable in phototherapy [34] …”
Section: Photothermally Responsive Nanomaterials For Therapy Applicatmentioning
confidence: 99%